TAFLURUT NIT-TOWARDS AN INCULTURATION THEOLOGY ON THE COMMUNION OF SAINTS FOR KEI PEOPLE IN EASTERN INDONESIA - Farneubun, Longginus (Animo Repository, 2024)
Ancestor veneration is considered by some to be a primitive custom, outdated, and with no relevance to modern society. In this study, however, the researcher will show that ancestor veneration is alive and practiced in various cultures, especially among Kei people in East Indonesia to this day. This research focuses on ancestor veneration (Taflurut Nit) of the Kei people vis-à-vis the Catholic Teachings on the Communion of Saints. Both the Kei ancestors and the Christian saints are revered because they are believed to be role models and wisdom figures for the members of their respective communities. Kei religious and cultural practices that focus on remembering, honoring, and expressing love for their ancestors and the saints have a significant impact on the lives of Kei Christians. The dissertation uses the process of inculturation to explore the potential of using the practices and beliefs of ancestor veneration among Kei people in re-articulating an aspect of the Christian Faith. With the mutual interaction between the Judeo-Christian Tradition of the Communion of Saints and the present practice of Ancestor Veneration (Taflurut Nit) among Kei people, an inculturated theology for Kei Christians in East Indonesia is being proposed in response to the new evangelization envisioned by the Church. This study uses the descriptive method of research where qualitative data were generated to describe the cultural practice of Taflurut Nit as one of the popular Kei Tribe rituals. Data were gathered through interviews of select members (i.e., traditional elders also regarded as kings, religious leaders, community leaders, government figures, and cultural observers) of the Kei community. These were recorded, coded, and thematically categorized. Interpretation and analysis were guided by the cultural exegesis process popularized by the theologian, José M. de Mesa. Available local literature was also helpful in enriching the information derived from the interviews conducted. To present a comprehensive understanding of the Church’s teachings on the Communion of Saints, a review of pertinent Church documents, books, journals, and articles was performed. Similar to the cultural exegesis process, the hermeneutics of appreciation was applied in discerning the primary themes from the Judaeo-Christian Tradition (JCT) which were used in mutual dialogue with the themes from Taflurut Nit. 2 Based on the results of the research, it was concluded that there are parallelisms between the Taflurut Nit of Kei people as a cult of respect for their ancestors and the teachings of the Catholic Church on the Communion of saints. First, both ancestors and saints are respected by the faithful as a form of deep love. Second, the belief in the existence of a Supreme Being (Duad Ler-vuan) as the creator of all things. Third, the role of ancestors and saints as intercessors (pengantara), model of virtuous living and companions in the journey of life emerged as common themes. Fourth, the exemplary legacy (warisan keteladanan) of ancestors and saints is passed on to their descendants or the faithful. And fifth, the meaning and implications of communion for both poles (persekutuan dan kekeluargaan yanur mangohoi), namely, harmony, unbreakable bond, faithfulness, and life-giving orientation that characterized their relationships. With the findings of this study, the proponent explored the potential of a widespread ancient practice, Taflurut Nit, as a starting point in doing theology that is sensitive to the present experience of the people. Besides the proposed inculturated theology on the Communion of Saints, it has also shown its broader spiritual implications and theological perspectives which, if developed, can benefit the whole Church. Keywords: Kei people, Taflurut Nit, Ancestor Veneration, Communion of Saints, Inculturation, Culture.